EDUCATIONAL DISCIPLINE "PHILOLOGY IN THE SYSTEM OF CONTEMPORARY HUMANITARIAN KNOWLEDGE": SPECIFICITY OF TEACHING IN A FOREIGN AUDIENCE - Umrzokova, Guljakhon (Журнал иностранных языков и лингвистики, 2021)
THIS ARTICLE IS ABOUT EDUCATIONAL DISCIPLINE "PHILOLOGY IN THE SYSTEM OF CONTEMPORARY HUMANITARIAN KNOWLEDGE": SPECIFICITY OF TEACHING IN A FOREIGN AUDIENCE